STEM education, environment, and industries – Toward achieving the Sustainable Development Goal through a knowledge transfer programme - Muhammad Abd Hadi, Bunyamin; Nor Hasmaliana, Abdul Manas; Nur Izyan, Wan Azelee; Nasratun, Masngut; Siti Fatimah Zaharah, Mohamad Fuzi; Nor Hasniza, Ibrahim; Johari, Surif; Wibowo, Firmanul Catur; Prahani, Binar Kurnia (EDP Sciences, 2024)
STEM education is important for protecting the environment. However, efforts to educate industries on environmental protection should be made to ensure sustainable practices within those industries. This study aims to report on efforts made to educate an industry on environmental protection using the case of wastewater treatment technology through a knowledge transfer programme (KTP) by a university. The KTP was conducted to expose industrial players, who were the research participants, to the issue of protecting the environment through the introduction of new technology in treating industrial wastewater. The main content included sharing knowledge on current bio-based technology and how the industry may be able to adopt the new technology for environmental protection. The participants were also exposed to a national study on the need for new technology in wastewater treatment. After the programme, they assessed the programme’s effectiveness and the outcomes. The key finding is that the KTP has increased the participants’ knowledge and awareness of the importance of adopting new technology in wastewater treatment as a means for achieving sustainable cities and communities. This effort is critical to ensuring the success of translating the Sustainable Development Goals (SDGs) among industries.